Security System Analysis against Flood Attacks Using TCP, UDP, and ICMP Protocols on Mikrotik Routers - Warid Yunus; Mohamad Efendi Lasulika (International Journal of Advances in Data and Information Systems, 2022)
Advances in information technology today require all existing computer networks to be able to show that the security system model continues to be considered very important for users who want security both from inside and outside the network. An attack on a network server can occur at any time, as for an attack that can cause a dangerous effect on a router, namely DDOS / flood by flooding the router with very many data packets so that the router can be paralyzed in terms of handling the network system. In this study, descriptive research was applied to obtain data directly by conducting flooding techniques and analyzing and designing flooding prevention techniques with filtering techniques. The application of filtering on the firewall on MikroTik can minimize attacks and prevention directly by dropping flooding packets automatically so that MikroTik performance remains stable